Women, Work, and Activism Chapters of an Inclusive History of Labor in the Long Twentieth Century - Archer, Rory; Baptista, Virgínia; Betas, Thanasis; Betti, Eloisa; Betti, Eloisa; Caligari, Marco; Faue, Elizabeth; Frisone, Anna; Grubački, Isidora; Kirkby, Diane; Laot, Françoise F.; Marques Alves, Paulo; et al. (Work and Labor - Transdisciplinary Studies for the 21st Century, 2022)
The thirteen critical and well-documented chapters of Women, Work and Activism examine women's labor struggle from late nineteenth-century Portuguese mutual societies to Yugoslav peasant women's work in the 1930s, and from the Catalan labor movement under the Franco dictatorship to workplace democracy in the United States. The authors portray women's labor activism in a wide variety of contexts. This includes spontaneous resistance to masculinist trade unionism, the feminist engagement of women workers, the activism of communist wives of workers, and female long-distance migration, among others. The chapters address the gendered involvement of working people in multiple and often precarious and unstable labor relations and in unpaid labor, as well as the role of the state and other institutions in shaping the history of women's labor. The book is an innovative contribution to both the new labor history and feminist history. It fully integrates the conceptual advances made by gender historians in the study of labor activism, driving home critiques of Eurocentric historiographies of labor to Europe while simultaneously contributing to an inclusive history of women's labor-related activism wherever to be found. Examining women's activism in male-dominated movements and institutions, and in women's networks and organizations, the authors make a case for a new direction in gender history